2017
DOI: 10.1002/sctm.16-0162
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Derived Precursors as a Source of Progenitors for Corneal Endothelial Regeneration

Abstract: Corneal blindness is the fourth leading cause of blindness in the world. Current treatment is allogenic corneal transplantation, which is limited by shortage of donors and immunological rejection. Skin‐derived precursors (SKPs) are postnatal stem cells, which are self‐renewing, multipotent precursors that can be isolated and expanded from the dermis. Facial skin may therefore be an accessible autologous source of neural crest derived cells. SKPs were isolated from facial skin of Wnt1‐Cre/Floxed EGFP mouse. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 39 publications
1
29
0
1
Order By: Relevance
“…Transplantation of cultured HCECs or possible precursor cells has been performed to overcome the shortage of donor tissue [59,[73][74][75][76]. Diverse research groups have identified markers for HCECs, including CD166, glypican 4 (GPC4), CD200, CD56, Integrin Subunit Alpha 3 (ITGA3), and CD49c [77][78][79][80][81].…”
Section: Endothelial Cell Density and Morphological Indicators As Gramentioning
confidence: 99%
“…Transplantation of cultured HCECs or possible precursor cells has been performed to overcome the shortage of donor tissue [59,[73][74][75][76]. Diverse research groups have identified markers for HCECs, including CD166, glypican 4 (GPC4), CD200, CD56, Integrin Subunit Alpha 3 (ITGA3), and CD49c [77][78][79][80][81].…”
Section: Endothelial Cell Density and Morphological Indicators As Gramentioning
confidence: 99%
“…Previously, Inagaki et al . 17 had acquired CEC-like cells from SKPs. However, there are some difference between our work and their work.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Inagaki et al . 17 had reported corneal endothelial-like cells could be derived from SKPs. Compared to their work, we use different derivation method, operation method and animal model.…”
Section: Introductionmentioning
confidence: 99%
“…Progenitors derived from corneal stroma can be differentiated into corneal endothelial cells. But, the access to these corneal progenitors is limited by a shortage of donors and by their limited proliferative capacity . SKPs isolated from the facial skin of mice can represent an accessible source of neural‐crest‐derived cells, which are able to differentiate into corneal endothelial‐like cells when cultured with retinoic acid and GSK 3‐β inhibitor.…”
Section: Potential Use Of Skps In Regenerative Medicinementioning
confidence: 99%